2011
DOI: 10.1080/14786419.2011.592836
|View full text |Cite
|
Sign up to set email alerts
|

Activity-guided isolation of antioxidant xanthones from Swertia chirayita (Roxb.) H. Karsten (Gentianaceae)

Abstract: An activity-guided isolation and purification process was used to identify the DPPH (l,l-diphenyl-2-picrylhydrazyl) radical-scavenging components of Swertia chirayita. A dry, whole plant of S. chirayita was extracted with different solvents and tested for its DPPH radical-scavenging activity. The acetone : water (8 : 2) extract showed the highest total phenolic content (TPC) and DPPH radical-scavenging activity, which was column chromatographed to obtain decussatin, swertianin, bellidifolin, isobellidifolin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…All the extracts showed variation in phenolic and flavonoid contents in all species with respect to polarity, which suggests that a diverse group of phenolic and flavonoid compounds is present in the studied species. Acetone (75%) has shown a better phenolic, flavonoid and antioxidant activity than other solvents, similar to the observations reported by Singh et al (2012) in S. chirayita.…”
Section: Dpph Radical-scavenging Activitysupporting
confidence: 88%
See 1 more Smart Citation
“…All the extracts showed variation in phenolic and flavonoid contents in all species with respect to polarity, which suggests that a diverse group of phenolic and flavonoid compounds is present in the studied species. Acetone (75%) has shown a better phenolic, flavonoid and antioxidant activity than other solvents, similar to the observations reported by Singh et al (2012) in S. chirayita.…”
Section: Dpph Radical-scavenging Activitysupporting
confidence: 88%
“…water. The total phenolics of S. chirayita using different solvents and different extraction techniques were studied by Phoboo et al (2010), Ghimire et al (2011), Chen et al (2011) and Singh et al (2012. All reviews of TPC show variation depending upon the extraction and solvent system used.…”
Section: Introductionmentioning
confidence: 99%
“…japonica and S . punctata (Sakamoto et al ., ; Li et al ., ; Singh et al ., ; Menkovic et al ., ). Swertianolin has been reported to possess hepatoprotective, anticholinesterase, antituberculosis, antioxidant, antiarrhythmic and antidiabetic effects (Brahmachari et al ., ; Li et al ., ; Urbain et al ., , ; Mukherjee et al ., ; Wani et al ., ; Wan et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Studies have shown that the four xanthones exhibit good DPPH (1, 1-Diphenyl-2-picrylhydrazyl) scavenging activity (Singh et al, 2012). Both bellidifolin and swertianolin exhibit significantly hepatoprotective effect (Zheng et al, 2014;.…”
Section: Introductionmentioning
confidence: 98%